Transformation pathways, detection, removal, and sustainable alternatives of 6PPD and its quinone derivative (6PPDQ): A comprehensive review - Kavya Somepalli; Gangadhar Andaluri (Emerging Contaminants, 2025)
N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6PPD) is a widely used antioxidant and antiozonant in vehicle tires, commonly used to enhance rubber durability and performance. However, its environmental transformation, particularly into 6PPD-Quinone (6PPDQ) through oxidative processes like ozonation, has emerged as a serious concern due to the acute toxicity in aquatic systems. 6PPDQ has been linked to significant mortality in sensitive fish species, including coho salmon, at 41 ng/L concentrations. This review synthesizes recent advances in the understanding of 6PPD degradation pathways, including ozonation, photodegradation, hydrolysis, microbial metabolism, and atmospheric reactions. This paper systematically examines the formation and characterization of various TPs and outlines the methods used for their detection across water, air, soil, sediments, and biota. It also evaluates the efficiency of treatment approaches such as advanced oxidation processes (AOPs), microbial degradation, adsorption, and membrane technologies for the removal of 6PPDQ from contaminated media. Additionally, emerging research on bio-based, synthetic, and engineered antioxidant alternatives to 6PPD is reviewed, with attention to their environmental compatibility and industrial feasibility. The paper concludes with a comprehensive outline of future research priorities focused on improving analytical detection, understanding long-term environmental fate and toxicity, optimizing treatment technologies, and guiding the development of safer alternatives. Collectively, this review provides a foundation for environmental risk assessment, regulatory policy development, and sustainable innovation in rubber manufacturing.